Biological detoxification of oxytetracycline using Achromobacter-immobilized bioremediation system. (April 2023) - Nguyen, Hiep T.; Siddiqui, Sharf Ilahi; Maeng, Sung Kyu; Oh, Seungdae
Abstract: Oxytetracycline (OTC) is widespread in the environment, posing potential ecological health risks. This work aimed to develop a bioremediation system that can biotransform and detoxify continuous OTC-bearing streams. An OTC-removing organism, Achromobacter sp. ONK, was isolated from activated sludge enriched with OTC. ONK removed OTC via co-metabolic biotransformation. A series of batch experiments were performed to determine the biotransformation kinetics (1.5–2.1 d −1 ) at varying levels of OTC and the optimal operating conditions (i.e., 2.0 g/L biomass and 0.2 g/L glucose as a carbon source) for OTC removal. A bioremediation system for treating continuous OTC streams was developed by immobilizing ONK using a natural alginate polymer. The immobilized-ONK bioremediation system demonstrated a > 60 % removal of OTC with a hydraulic retention time of 10 h and detoxified OTC using two novel transformation pathways that were validated by both structure-based modeling and experimental results. This study has practical implications for the development of an effective bioremediation process for detoxifying pharmaceutical waste streams. Graphical abstract: Unlabelled Image Highlights: Achromobacter sp. ONK removed OTC via co-metabolic biotransformation. ONK exhibited two novel biodegradation pathways with high transformation rates. The operating conditions enhancing OTC removal kinetics were elucidated. An ONK-immobilized bioremediation system was developed in continuous flow mode. The bioremediation system achieved biotransformation-enabled OTC detoxification.